Childhood Physical Victimization and Relationship Dysfunction in Justice-Involved Women: A Path Analysis - Megan Foster; Emily Salisbury (Social Sciences)
(1) Background: The pathways perspective considers how different biological, psychological, and social experiences affect women compared to men and how these experiences can lead to initial justice-involvement and recidivism. The relational model provides context for understanding women’s pathways to the criminal justice system. Interpersonal relationships have strong effects on women’s likelihood to offend. The relationship between risk factors like childhood victimization, adult relationship dysfunction, self-esteem, and self-efficacy are less clear. (2) Methods: Using a sample of justice-involved women, the current study uses a path analysis to investigate the impact of childhood physical abuse on adult relationship dysfunction and if this relationship is mediated by self-esteem and/or self-efficacy. (3) Results: Childhood physical abuse was found to have a significant negative effect on self-esteem and self-efficacy as well as a significant positive effect on adult relationship dysfunction. Indirect relationships were not significant. (4) Conclusions: The current study verifies previous pathways analysis but does not support self-esteem and self-efficacy as mediators of adult relationship dysfunction.